Engaging stakeholders to inform national implementation of critical time intervention in a program serving homeless-experienced Veterans - Gabrielian, Sonya; Cordasco, Kristina M.; Finley, Erin P.; Hoffmann, Lauren C.; Harris, Taylor; Calderon, Ronald A.; Barnard, Jenny M.; Ganz, David A.; Olmos-Ochoa, Tanya T. (Frontiers in Psychology, 2022)
The Veterans Affairs (VA) Grant and Per Diem Case Management “Aftercare” program provides six months of case management for homeless-experienced Veterans (HEVs) transitioning to permanent housing, with the aim of decreasing returns to homelessness. Implementing Critical Time Intervention (CTI)—an evidence-based case management practice—would standardize care across the 128 community-based agencies that provide Aftercare services. To prepare for national CTI implementation in Aftercare, guided by Replicating Effective Programs (REP), we conducted a four-site pilot in which we adapted a CTI implementation package (training, technical assistance, and external facilitation); characterized stakeholder perspectives regarding the acceptability and appropriateness of this package; and identified contextual factors that affected CTI implementation. We engaged a stakeholder workgroup to tailor existing CTI training and technical assistance materials for Aftercare. To provide tailored support for providers and leaders to adopt and incorporate evidence-based practices (EBPs) into routine care, we also developed external facilitation materials and processes. Over nine months, we implemented this package at four sites. We conducted semi-structured interviews at pre-implementation, mid-implementation, and six months post-implementation, with HEVs (n=37), case managers (n=16), supervisors (n=10), and VA leaders (n=4); these data were integrated with templated reflection notes from the project facilitator. We used rapid qualitative analysis and targeted coding to assess the acceptability and appropriateness of CTI and our implementation package and identify factors influencing CTI implementation. Stakeholders generally found CTI acceptable and appropriate; there was consensus that components of CTI were useful and compatible for this setting. To adapt our implementation package for scale-up, this pilot highlighted the value of robust and tangible CTI training and technical assistance—grounded in real-world cases—that highlights the congruence of CTI with relevant performance metrics. Variations in agency-level contextual factors may necessitate more intense and tailored supports to implement and sustain complex EBPs like CTI. Processes used in this pilot are relevant for implementing other EBPs in organizations that serve vulnerable populations. EBP scale-up and sustainment can be enhanced by engaging stakeholders to tailor EBPs for specific contexts; pilot testing and refining implementation packages for scale-up; and using qualitative methods to characterize contextual factors that affect EBP implementation.